Diklat Sebagai Strategi Pengembangan Sumber Daya Manusia: Studi Kualitatif Tentang Efektivitas Diklat - Aprila, Gusti; Juliani, Duwi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effectiveness of Diklat as a human resource development strategy. This qualitative study uses interview and observation methods to collect data from Diklat participants and instructors. The results show that Diklat is effective in improving participants’ abilities and skills, as well as increasing motivation and job satisfaction. However, this study also found several challenges faced in implementing Diklat, such as the lack of adequate facilities and infrastructure. This study provides recommendations to improve the effectiveness of Diklat by improving facilities and infrastructure, as well as enhancing instructor quality